Integrated Modelling Platform for Dynamic Performance Assessment of Floating Wind Turbines. (2015) - Endegnanew, Atsede G.; Satertro, Kristian; Gjerde, Sverre; Svendsen, Harald; Anaya-Lara, Olimpo; Tande, John O.; Uhlen, Kjetil; Gjolmesli, Svein
Abstract: The paper presents an integrated modelling platform that can be used to assess the dynamic performance of an offshore wind turbine mounted on a spar-buoy type floater. Sub-models of generator and converter controllers and the power network are combined with a state-of-the-art numerical simulation of the hydro-, aero- and structural dynamic behavior of the floating wind turbine, using FEDEM Windpower software. The aim is to provide a tool that allows analyzing response of floating turbines to grid faults, interactions and potential conflicts between controllers. A study case of grid disturbance was conducted to illustrate the applicability of an integrated model. A grid fault that lasted 100ms and resulted in 50% residual voltage at the grid connection point was applied, and wind turbine operation both in still water and in large sea wave conditions were analyzed. The results show that the turbine was capable of riding through voltage-dips without severe effects on the electrical or mechanical systems. A significant, but not critical, dip in the tower bending moment was observed. The most affected component of the bending moment is around the axis of the rotor, which is directly related to the loss of generator torque due to the grid disturbance event.